Pemanfaatan Lahan Asmantoga (Asuhan Mandiri Tanaman Obat Keluarga) Dengan Metode ABCD - Ulfa Ulfa; Rahmat Irsyada; Nurul Hafidhin (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Independent Upbringing of Family Medicinal Plants (Asmantoga) is a plant cultivated by the surrounding community and cadres of Bojonegoro sources of corn which has medicinal properties and can be used for health. Besides that, Asmantoga plants are natural medicines and do not contain chemicals. Under these circumstances, the servants made an innovation in the Asmantoga Park to turn the medicinal plant area of the Sumberagung village family from Bojonegoro into an Asmantoga Educational Park. And also conduct independent care as an effort to change the paradigm of curative medicine, to become promotive and preventive, which is beneficial for efficiency and effectiveness for the surrounding community and Sumberagung cadres.This service aims to find out the development of family medicinal plants in the village of Sumberagung, Dander Bojonegoro sub-district, to find out how to increase community knowledge about the benefits of self-care for family medicinal plants in Sumberagung Village, Dander Bojonegoro District.The community service partners here are Village Officials, and Asmantoga Cadres of Sumberagung Village, Dander Bojonegoro District.The methodology used in community service in Sumberagung village is the ABCD (Asset Based Community Development) method.The results of the Asmantoga land use activities have made the residents a little more concerned with the Asmantoga land use. Pengabdi also held a health seminar with the theme "keep your health with family medicinal plants" with Sumberagung village health workers in order to introduce to the community how important it is to preserve family medicinal plants.